THE SECRETARIAT OF THE ANTARCTIC TREATY: ACHIEVEMENTS AND WEAKNESSES THREE YEARS AFTER ITS ESTABLISHMENT - VIGNI, PATRIZIA (BRITISH INSTITUTE OF INTERNATIONAL AND COMPARATIVE, 2007)
The establishment of the Antarctic Treaty Secretariat has promoted the institutional development of the Antarctic Treaty System. This organ is an atypical solution within the framework of international law. It may be successly applied in other international legal regimes